2015
DOI: 10.5194/amt-8-1303-2015
|View full text |Cite
|
Sign up to set email alerts
|

Measuring acetic and formic acid by proton-transfer-reaction mass spectrometry: sensitivity, humidity dependence, and quantifying interferences

Abstract: Abstract. We present a detailed investigation of the factors governing the quantification of formic acid (FA), acetic acid (AA), and their relevant mass analogues by proton-transfer-reaction mass spectrometry (PTR-MS), assess the underlying fragmentation pathways and humidity dependencies, and present a new method for separating FA and AA from their main isobaric interferences. PTR-MS sensitivities towards glycolaldehyde, ethyl acetate, and peroxyacetic acid at m/z 61 are comparable to that for AA; when presen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(103 citation statements)
references
References 62 publications
10
81
3
Order By: Relevance
“…Higher fragmentation in the PTR-TOF (61.0284 Da), when compared to the PTR-Quad (60.5 to 61.5 Da), could account for a part of the lower acetic acid fluxes with the EC method. However, even when the acetic acid main fragment C 2 H 3 O + (Baasandorj et al, 2015) is taken into account, in addition to the signal from the parent mass, the EC fluxes are still lower than the SLP results. Another uncertainty comes from the lack of acetic acid in the calibration standard.…”
Section: Comparison Between Ptr-tof and Ptr-quad Measurementsmentioning
confidence: 73%
See 1 more Smart Citation
“…Higher fragmentation in the PTR-TOF (61.0284 Da), when compared to the PTR-Quad (60.5 to 61.5 Da), could account for a part of the lower acetic acid fluxes with the EC method. However, even when the acetic acid main fragment C 2 H 3 O + (Baasandorj et al, 2015) is taken into account, in addition to the signal from the parent mass, the EC fluxes are still lower than the SLP results. Another uncertainty comes from the lack of acetic acid in the calibration standard.…”
Section: Comparison Between Ptr-tof and Ptr-quad Measurementsmentioning
confidence: 73%
“…Kajos et al (2015) reported similar discrepancies in toluene + p-cymene concentration measurements with the PTR-Quad at the site. Also, acetic acid fragments when measured with the PTR method (Baasandorj et al, 2015). Higher fragmentation in the PTR-TOF (61.0284 Da), when compared to the PTR-Quad (60.5 to 61.5 Da), could account for a part of the lower acetic acid fluxes with the EC method.…”
Section: Comparison Between Ptr-tof and Ptr-quad Measurementsmentioning
confidence: 99%
“…In this case the fragmentation pattern is not accounted for and all fragments have to be added up to arrive at the total flux, excluding those that could be associated with calibrated compounds. Two exceptions were made: the sensitivity for acetic acid was halved (9.55 ncps ppb −1 ) as it was not calibrated and its major fragment (C 2 H 3 O + ; Baasandorj et al, 2015) was disregarded. For ethanol (C 2 H 7 O + 1 ) the methanol sensitivity was used.…”
Section: Calibration and Concentration Calculationmentioning
confidence: 99%
“…Table S1 provides a summary of literature surface and aircraft measurements for GA in urban, biomass burning, biogenic, and mixed environments. GA's primary loss is by HO oxidation and wet deposition (Bacher et al, 2001). The effective Henry's Law constant for GA (70 M hPa −1 ) is surprisingly large (Betterton and Hoffmann, 1988) and an order of magnitude larger than that for HAc (7.8 M hPa −1 ) at a temperature of 288 K (Johnson et al, 1996;results below).…”
Section: Treadaway Et Al: Multi-ion Cims Organic Acids and Peroxidesmentioning
confidence: 99%